ФРАЗЕОЛОГИЗМЛЕРДИҢ СЕМАНТИКАСЫНДА ЭМОЦИОНАЛЬЛЫҚ – ЭКСПРЕССИВЛИК МӘНИЛЕР - Пирниязова, А.Қ. (FAN va JAMIYAT, 2018)
The article deals with emotional–expressive meanings in the semantics of Karakalpak phraseological units. The variety of phraseological units with emotive meaning has been proved by the examples from the works of fiction.